Maternal Dissatisfaction About Toddler’s Body Size And Its Relationship To Children’s Eating Behaviours - E, Wulandari; B, Wiboworini; V, Widyaningsih (International Journal of Human and Health Sciences (IJHHS), 2023)
The fulfilment of toddlers’ nutritional needs is very dependent on their parents. Parental dissatisfaction can affect feeding practices and food choices for her children that are related to eating behaviour. This study aimed to analyzed the relationship between maternal satisfaction of children’s body size and their children’s eating behaviour. This cross-sectional study involved 126 pairs of mother-toddler ages 24-59 months. Mother’s satisfaction was assessed using Toddler Silhouette Questionnaire, while their children’s eating behaviour was assessed using the Children’s Eating Behaviour Questionnaire (CEBQ). The result shows that 77.6% of mothers who have well-nourished children desire a heavier child. There is a positive relationship between maternal satisfaction with Food Avoidance behaviour (p<0.01) at subscale Slowness in Eating (p<0.01), Food Fussiness (p<0.05) and Emotional Eating (p<005). Mother who wants their children to be heavier tends to have children who are food avoidance, slow to eat, picky eaters and emotional eating. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 157-161